Fixed point results for ordered S-G-contractions in ordered metric spaces - Vetro, Francesca (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we prove existence and uniqueness of fixed point in the setting of ordered metric spaces. Precisely, we combine the recent notions of (F,φ)-contraction and Z-contraction in order to introduce the notion of ordered S-G-contraction. Then we use the notion of ordered S-G-contraction to show existence and uniqueness of fixed point. We stress that the notion of ordered S-G-contraction includes different types of ordered contractive conditions in the existing literature. Also, we give some examples and additional results in ordered partial metric spaces to support the new theory.
Keywords: ordered S-G-contraction; fixed point; ordered metric space; nonlinear contraction